Governance and Curriculum Adaptation in Kutubussalaf Education: A Case Study of Darussalam Islamic Boarding School - Sari, Linda Puspita; Nahdliyah, Amirotun (Islamic Studies and Development Center in collaboration with Department of Islamic Education Universitas Negeri Padang, 2026)
This study investigates the governance and curriculum adaptation of Kutubussalaf education within Darussalam Islamic Boarding School, emphasizing how classical Islamic scholarly traditions are preserved while selectively responding to contemporary educational demands. Employing a qualitative case study approach, data were collected through direct observation, institutional document analysis, and in-depth interviews with 12 purposively selected informants, including the kyai, teachers, administrators, and students. Data analysis utilized the Miles and Huberman interactive model, enabling a comprehensive understanding of pesantren governance and curriculum practices. The findings reveal that governance is implemented through a traditional-participatory management model, with the kyai serving as the central authority in scholarly and strategic decision-making. Curriculum planning and implementation are not strictly based on formal documentation but are embedded in scholarly traditions, daily practices, and pesantren culture. Adaptation occurs contextually through adjustments in the depth of kitab content, flexible teaching methods, and the strengthening of scholarly forums such as bahtsul masail to address contemporary religious issues. The study concludes that Kutubussalaf governance enables the integration of classical kitab curriculum with flexible scheduling, teaching methods, and role distribution among educators, offering practical insights for other salafiyah pesantren in designing curriculum decision-making mechanisms and teacher management while maintaining classical scholarly structures.